2020
DOI: 10.1128/mbio.03246-19
|View full text |Cite|
|
Sign up to set email alerts
|

Autoantibody-Mediated Erythrophagocytosis Increases Tuberculosis Susceptibility in HIV Patients

Abstract: Macrophage dysfunction is associated with increased tuberculosis (TB) susceptibility in patients with human immunodeficiency virus (HIV) infection. However, the mechanisms underlying how HIV infection impairs macrophage function are unclear. Here, we found that levels of autoantibodies against red blood cells (RBCs) were significantly elevated in patients with HIV as determined by direct antiglobulin test (DAT). DAT positivity was significantly associated with TB incidence in both univariate and multivariate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…Finally, iron supplementation in such cases is still a matter of debate, with inconsistent results reported by clinical trials. The probable determinants of anemia in the context of HIV/AIDS and TB are likely multifactorial and involve several factors including nutritional status ( 31 ), chronic inflammation and antibody-mediated erythrophagocytosis ( 32 ). Our results demonstrated that anemic patients also exhibit lower counts of other cell types, suggesting that a global effect on the bone marrow may be occurring.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, iron supplementation in such cases is still a matter of debate, with inconsistent results reported by clinical trials. The probable determinants of anemia in the context of HIV/AIDS and TB are likely multifactorial and involve several factors including nutritional status ( 31 ), chronic inflammation and antibody-mediated erythrophagocytosis ( 32 ). Our results demonstrated that anemic patients also exhibit lower counts of other cell types, suggesting that a global effect on the bone marrow may be occurring.…”
Section: Discussionmentioning
confidence: 99%
“…The link between the inhibition of cellular ATP production and autophagy were further confirmed by inhibitors of the electron transport chain (Fig. S6 C-D).Next, we then used a stably transformed mRFP-GFP-LC3 reporter in the THP-1 macrophages(26) to further determine the effect of MFN1 on autophagy flux. Silencing of MFN1 significantly reduced the numbers of autophagosomes and autolysosomes, which formed puncta structures in H37Ra-infected cells,(Fig.…”
mentioning
confidence: 72%
“…Nonadherent cells were washed twice with prewarmed RPMI‐1640 and adherent cells were treated with 50 ng/ml human macrophage CSF (PeproTech) in RPMI‐1640 with 10% fetal calf serum and 2 mM l ‐glutamine for adhesion processing. The monocytes were incubated for 5 days to differentiate into human monocyte‐derived macrophages (hMDMs) at 37°C in an atmosphere of 5% CO 2 16 …”
Section: Methodsmentioning
confidence: 99%
“…Digital images of the protein bands were acquired using the Chemiluminescence Image System (Minichem™, China). 16…”
Section: Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation